Cuba en el contexto regional posterior a la VII Cumbre de las Américas en Panamá (Tema Central) - Bullón Méndez, Mariano (2015)
The article contains a briefing about the relations between Cuba and the United States, from 1959 until now (2015), in order to make a referenceto the circumstances that allowed arriving at December 17 (17-D), a turning point for the two countries bilateral relations. This paper provides an overview of plausible changes in the hemispheric system under the process of restoration of diplomatic relations between Cuba and the United States, in the context of the recent VII Summit of the Americas. Because of the above, the work ahead in their final moments, a set of challenges to face in this process of change in the region.